Association of DNA Methylation in Blood Pressure-Related Genes With Ischemic Stroke Risk and Prognosis - Zhang, Huan; Mo, Xingbo; Wang, Aili; Peng, Hao; Guo, Daoxia; Zhong, Chongke; Zhu, Zhengbao; Xu, Tan; Zhang, Yonghong (Frontiers in Cardiovascular Medicine, 2022)
Background: A genome-wide association study identified 12 genetic loci influencing blood pressure and implicated a role of DNA methylation. However, the relationship between methylation and ischemic stroke has not yet been clarified. We conducted a large-sample sequencing study to identify blood leukocyte DNA methylations as novel biomarkers for ischemic stroke risk and prognosis based on previously identified genetic loci. Methods: Methylation levels of 17 genes were measured by sequencing in 271 ischemic stroke cases and 323 controls, and the significant associations were validated in another independent sample of 852 cases and 925 controls. The associations between methylation levels and ischemic stroke risk and prognosis were evaluated. Results: Methylation of AMH, C17orf82, HDAC9, IGFBP3, LRRC10B, PDE3A, PRDM6, SYT7 and TBX2 was significantly associated with ischemic stroke. Compared to participants without any hypomethylated targets, the odds ratio (OR) (95% confidence interval, CI) for those with 9 hypomethylated genes was 1.41 (1.33–1.51) for ischemic stroke. Adding methylation levels of the 9 genes to the basic model of traditional risk factors significantly improved the risk stratification for ischemic stroke. Associations between AMH, HDAC9, IGFBP3, PDE3A and PRDM6 gene methylation and modified Rankin Scale scores were significant after adjustment for covariates. Lower methylation levels of AMH, C17orf82, PRDM6 and TBX2 were significantly associated with increased 3-month mortality. Compared to patients without any hypomethylated targets, the OR (95% CI) for those with 4 hypomethylated targets was 1.12 (1.08–1.15) for 3-month mortality (P = 2.28 × 10-10). Conclusion: The present study identified blood leukocyte DNA methylations as potential factors affecting ischemic stroke risk and prognosis among Han Chinese individuals.